STRATEGI PEMASARAN DIGITAL DALAM MENINGKATKAN DAYA SAING PERUSAHAAN DI PASAR GLOBAL (STUDI PADA PT. SELAMAT SEMPURNA TBK) - Solihin, Ahmad; Sari, Meci Nilam (Universitas Ratu Samban, 2024)
In the era of globalization and rapidly advancing technology, industries and companies are required to continuously innovate their marketing strategies. In this context, it is essential for PT. Selamat Sempurna Tbk to understand and implement appropriate digital marketing strategies to enhance brand awareness, reach more potential customers, and build stronger relationships with existing customers. The purpose of this research is to investigate the marketing strategies employed by PT. Selamat Sempurna Tbk in facing global competition and to determine whether the strategies implemented by this company are significantly effective in addressing global competition. This study utilizes a descriptive qualitative research method. Data collection techniques are conducted through in-depth interviews, observations, and documentation related to the company. As for the data analysis method, this research employs a descriptive approach. The results of this study indicate that PT. Selamat Sempurna Tbk actively adopts and integrates digital technology and market data analysis to reach and participate in the global market. The company also demonstrates a high level of adaptation by continuously developing innovations to tackle various digital marketing challenges in the global market, thereby significantly enhancing its competitiveness.